EFEK EKSTRAK TUBER SARANG SEMUT (Myrmecodia tuberosa (non Jack) Bl.) TERHADAP PROFIL SEL TCD4+ DAN TCD8+ TIKUS SPRAGUE DAWLEY YANG DIINDUKSI DOKSORUBISIN - , sumardi, Dr. Ediati Sasmito, SE., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Doxorubicin (Dox) is an important anticancer drug. One of side effects known for Dox is immune-suppressing activity, which increases the risk of infection. Combination between Dox with immunomodulator herbs may reduce the side effects. This study aimed to explore effect of sarang semut tuber extract on TCD4+ and TCD8+ cell profiles of Dox-induced Sprague Dawley (SD) rats in vivo. The study was done in two stages. The first stage was to explore the extract and fractions of sarang semut tubers activities as immunomodulatory agents by an in vitro method, and the second stage was to explore the effect of active extract on TCD4+ and TCD8+ cell profiles on Dox-induced SD rats in vivo. The study was started by macerating dried powder in ethanol 95%. The solvent was evaporated and crude extract (EMT) was partitioned with equal volume n-hexane:metanol 90% to yield purified extract (ETH) and n-hexane fraction (FHE). ETH was further fractionated with ethyl acetate:water to yield ethyl acetate fraction (FEA), and water fraction (FAI). The extract and fractions were tested on phagocytosis activity of macrophage cells and proliferation of lymphocyte cells by in vitro method. Total phenolic and flavonoid contents of extract and fraction were determined to investigate the correlation to the immunomodulatory activity. Active extract was further for tested its effect on TCD4+ and TCD8+ cells profile on Dox-induced SD rats in vivo. The result showed crude extract and fraction had promising activities on immunomodulator in vitro. ETH at 20 Âµg/mL showed the highest activities on phagocytosis by macrophage cells, while FEA at 100 Âµg/mL had the highest activities on proliferation of lymphocyte cells. The highest total phenolic content was EMT (3.75%) while FEA (2.15%) had flavonoid. In vivo assay showed that ETH could maintain the number of TCD4+ cells, but unable to maintain the number of TCD8+ cells. TLC profile of the active fraction, FEA showed the presence of steroid/terpenoid, phenolic and flavonoid. As the conclusion, sarang semut tuber extract is a potential immunomodulatory agent and may act as cochemotherapy in Dox use.